Cash Crop Productivity Analysis of Agroforestry System in Samboja, Kutai Kartanegara District - indra wahyu (Jurnal Agroekoteknologi Tropika Lembab, 2018)
The research objectives were to: 1) find out and analyze the productivity of cash crops in agroforestry and monoculture systems; 2) determine the selection of cash crops in Amborawang Laut Village.  The study was conducted from September to November 2015.  Determination of respondents using census methods.  The number of respondents was 20 farmers, consisted of 10 farmers for each system (agroforestry and monoculture).  The data collected was primary and secondary data.  Data collection methods were carried out through interview, observation, and documentation.  Data were analyzed using an independent t-test.  The results showed that the productivity of cash crops in agroforestry system for three years (2013-2015) for string beans, beans, bitter melon, squash, cayenne pepper, eggplant pondoh, and cucumber respectively was 13,64; 11,86; 11,17; 14,00; 18,05; 11,75; dan 11,50 Mg ha-1, while the monoculture system was 7,01; 10,50; 10,50; 12,63; 10,45; 12,33; dan 10,58 Mg ha-1.  The selection of cash crops by farmers in agroforestry and monoculture systems was based on market demand, namely types of plant that are easily marketed and sought after by consumers.